Treatment of Meniscal Deficiency with Meniscal Allograft Transplantation and Femoral Osteotomy in a Patient with History of Lateral Discoid Meniscus: 15-Year Follow-up Case Report. Issue 1 (January 2020) - Zaffagnini, Stefano; Espinosa, Maximiliano; Neri, Maria Pia; Marcacci, Maurilio; Grassi, Alberto
Abstract : Case: A 15-year-old woman with multiple arthroscopic procedures for left lateral discoid meniscus since the age of 9 presented with pain, swelling, and mechanical symptoms. A meniscal allograft transplantation (MAT) and lateral opening-wedge femoral osteotomy was performed. At the 6-year follow-up, the patient presented a visual analog scale (VAS) score of 0, subjective International Knee Documentation Committee (IKDC) of 88, and Lysholm of 95. At 15-year follow-up, the VAS score was 0, subjective IKDC 85.1, and Lysholm 86. Conclusions: MAT associated with femoral osteotomy was an effective procedure in this patient with pain and functional limitation after total meniscectomy in the setting of discoid meniscus and valgus malalignment. Good clinical and magnetic resonance imaging-related outcomes were achieved at the intermediate and long-term follow-up.